LEXIN i Norge – Hva sier brukerne? - Bjørneset, Tove (Nordiske Studier i Leksikografi, 2018)
The original Swedish dictionary series LEXIN was launched in the 1980’s, designed specifically for minority language immigrants living in Sweden. In 1996, The Norwegian Ministry for Education, Research and Church Affairs initiated a corresponding Norwegian project at The Norwegian Term Bank. The project has since continued in the same environment. At present it is a part of the university-owned company Uni Research, and it is owned and funded by The Norwegian Directorate for Education and Training (Utdanningsdirektoratet). The Norwegian series consists of dictionaries from Norwegian Bokmål and Nynorsk into 16 target languages, and more languages are forthcoming. Since the launch in 2002 the dictionary users have been able to contact the project group directly through the project’s website. The user dialogue has proven to be of great value. Two user surveys have also contributed to improve our knowledge about the user needs and about how they benefit from using Norwegian LEXIN.